Comparison of psychological distress, emotional regulation difficulties and distress tolerance in pregnant women with and without thyroid disorder - Ramezani, Soghra; Haji Alizadeh, Kobra; Ahmad Nia, Fatemeh (Psychology of Woman Journal, 2022)
Considering the sensitivity during pregnancy for mother and baby, as well as the importance of investigating and controlling the consequences of thyroid gland dysfunction in pregnant women, the purpose of this study was to compare psychological distress, emotional regulation difficulties, and distress tolerance in pregnant women with and without thyroid gland dysfunction. The research method was causal-comparative. The statistical population was all pregnant women referred to Shariati Hospital and health centers in Bandar Abbas city. From this population, 92 pregnant women - with and without thyroid gland disorder - were selected by purposive sampling method (46 participants with thyroid gland disorder and 46 without disorder). The research tools included: Kessler Psychological Distress Scale (KPDS-10), Emotional Regulation Difficulty Scale (DERS-36), and Distress Tolerance Scale (DTS-15). The data analysis method was a multivariate variance analysis (MANOVA). The results showed that psychological distress and emotional regulation difficulties in pregnant women with thyroid gland disorder are significantly higher (p<0.01) than in pregnant women without thyroid gland disorder, and their distress tolerance is lower (p<0.05). According to the results, educational and therapeutic plans, individually and in groups, for pregnant women with thyroid gland disorder can be among the strategies of attention of health centers related to the health of pregnant women.